Genome‐wide analyses in neuronal cells reveal that upstream transcription factors regulate lysosomal gene expression. (11th February 2016) - Yamanaka, Tomoyuki; Tosaki, Asako; Kurosawa, Masaru; Shimogori, Tomomi; Hattori, Nobutaka; Nukina, Nobuyuki
Abstract : The upstream transcription factors (USFs) USF1 and USF2 are ubiquitously expressed transcription factors that are characterized by a conserved basic helix‐loop‐helix/leucine zipper DNA‐binding domain. They form homo‐ or heterodimers, and recognize E‐box motifs to modulate gene expression. They are known to regulate diverse cellular functions, including the cell cycle, immune responses and glucose/lipid metabolism, but their roles in neuronal cells remain to be clarified. Here, we performed chromatin immunoprecipitation of USF1 from mouse brain cortex. Subsequent promoter array analysis (ChIP‐chip) indicated that USF1 exclusively bound to the CACGTG E‐box motifs in the proximal promoter regions. Importantly, functional annotation of the USF1‐binding targets revealed an enrichment of genes related to lysosomal functions. Gene expression array analysis using a neuronal cell line subsequently revealed that knockdown of USFs de‐regulated lysosomal gene expression. Altered expression was validated by quantitative RT‐PCR, supporting the conclusion that USFs regulate lysosomal gene expression. Furthermore, USF knockdown slightly increased LysoTracker Red staining, implying a role for USFs in modulating lysosomal homeostasis. Together, our comprehensive genome‐scale analyses identified lysosomal genes as targets of USFs in neuronal cells, suggesting a potential additional pathway of lysosomal regulation. Database: The data for the gene expression array and ChIP‐chip have been submitted to the Gene Expression Omnibus (GEO) under accession numbersGSE76615 andGSE76616, respectively. Abstract : Upstream stimulating factors, USF1/2, are ubiquitous transcription factors binding to E‐box motifs. To clarify their neuronal functions, we performed ChIP‐chip and gene expression array analyses using neuronal cells. Functional annotation revealed high enrichment of lysosomal genes in both analyses, and their altered expressions were confirmed by qRT‐PCR. Our observations suggest USF1/2 as novel modulators of lysosomal genes in neuronal cells.